1999
DOI: 10.1055/s-1999-9890
|View full text |Cite
|
Sign up to set email alerts
|

Spiral-CT der Kopf-Hals-Region: Vorteile der arteriellen Frühphase bei der Detektion von Plattenepithelkarzinomen

Abstract: Contrast-enhanced special CT permits accurate morphologic assessment (size, infiltration) of pharyngeal and supraglottic laryngeal squamous cell carcinoma, while pathologic lymph nodes already have a sufficient contrast enhancement for the detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…[ 15 ] Conrad et al . [ 16 ] described the superiority of scans obtained 20 s after the start of injection over scans acquired 70 s after the start. They showed that the contrast between squamous cell carcinoma of the head and neck and surrounding soft-tissue structures was significantly better on the arterial phase scans (20 s delay) than on the later scans (70-s delay).…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Conrad et al . [ 16 ] described the superiority of scans obtained 20 s after the start of injection over scans acquired 70 s after the start. They showed that the contrast between squamous cell carcinoma of the head and neck and surrounding soft-tissue structures was significantly better on the arterial phase scans (20 s delay) than on the later scans (70-s delay).…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to the majority of authors, one group [3] claims that an early arterial phase (start delay of 20 s) improves the detection of neck primaries by comparing it with a late phase (70 s); however, the injection time was only 27 s (80 ml contrast agent at 3 ml/s) and nothing is said about the size and the T-stadium of the 20 tumors involved in the study. Our results do not support an early arterial phase for a better delineation of neck tumors.…”
Section: Contrast Performancementioning
confidence: 96%
“…To date, an increasing number of neck tumors are examined with spiral CT. The main reasons for this development are a faster examination, consecutively less swallowing artifacts, the possibility of e-phonation and/or Valsalva maneuver, and an improved exploitation of a single bolus with a smaller total volume of contrast agent as compared with sequential CT. With the advent of fast spiral CT of the neck, some authors recommend early scans during the vascular phase in order to achieve the best possible contrast between lymph nodes and neck vessels [3,4]. One group states that the detection of cervical lymph nodes is more important than the detection and/or exact delineation of neck primaries [4]; however, these authors do not realize that neck primaries are to be staged based on either the greatest diam-1988 b a c Fig.…”
Section: General Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies mag die Tatsache erklären, warum in unserer Studie virtuell-laryngoskopisch der Stenosegrad in zwei Fällen im Vergleich zur fiberoptischen Laryngoskopie um je einen Grad überbewertet wurde.Axiale CT-Schnittbilder sind für die Beurteilung von Pathologien des Halses unentbehrlich, da sie eine Vielzahl von Informationen liefern, die über die innere Oberflächenrekonstruktion der oberen Luftwege hinausgehen[15,16]. Zusätzlich zur endoluminalen Beurteilung der Luftwege werden wichtige Strukturen in der Umgebung wie Gefäûe, Lymphknoten, Schilddrüse und Ösophagus mitbeurteilt.…”
unclassified